Bank risk and monetary policy - Yener Altunbas; Leonardo Gambacorta; David Marqués-Ibá\~nez (European Central Bank (ECB), 2009)
We find evidence of a bank lending channel for the euro area operating via bank risk. Financial innovation and the new ways to transfer credit risk have tended to diminish the informational content of standard bank balance-sheet indicators. We show that bank risk conditions, as perceived by financial market investors, need to be considered, together with the other indicators (i.e. size, liquidity and capitalization), traditionally used in the bank lending channel literature to assess a bank's ability and willingness to supply new loans. Using a large sample of European banks, we find that banks characterized by lower expected default frequency are able to offer a larger amount of credit and to better insulate their loan supply from monetary policy changes.
Keywords: E44; E55; 330; bank; bank lending channel; monetary policy; risk; Geldpolitik; Kreditgeschäft; Geldpolitische Transmission; Bankrisiko; EU-Staaten